Income Taxes, Sorting, and the Costs of Housing: Evidence from Municipal Boundaries in Switzerland - Christoph Basten; Maximilian von Ehrlich; Andrea Lassmann (Center for Economic Studies and ifo Institute (CESifo), 2014)
This paper provides novel evidence on the role of income taxes for residential rents and spatial sorting. Drawing on comprehensive apartment-level data, we identify the effects of tax differentials across municipal boundaries in Switzerland. The boundary discontinuity design (BDD) corrects for unobservable location characteristics such as environmental amenities or the access to public goods and thereby reduces the estimated response of housing prices by one half compared to conventional estimates: we identify an income tax elasticity of rents of about 0.26. We complement this approach with census data on local sociodemographic characteristics and show that about one third of this effect can be traced back to a sorting of high-income households into low-tax municipalities. These findings are robust to a matching approach (MBDD) which compares identical residences on opposite sides of the boundary and a number of further sensitivity checks.
Keywords: H71; H24; R21; R38; C14; 330; local taxation; income taxation; housing prices; income sorting; boundary discontinuity design; spatial differencing